Prevalence of hyponatremia in hospitalized patients with coronavirus disease 2019; a multicenter study - Sepideh Hajian; Ali Sarbazi-Golezari; Maryam Karbasi (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: In patients with coronavirus disease 2019 (COVID-19), the prevalence of hyponatremia has been reported with varying outcomes. Objectives: The aim of this study was to evaluate the prevalence of hyponatremia in hospitalized patients with COVID-19. Patients and Methods: In this multicenter cross-sectional study, information about hospitalized patients with COVID-19 admitted between March 2020 and September 2020, including age, gender, and serum levels of sodium, creatinine, and potassium, as well as blood urea nitrogen (BUN), was analyzed, while P value level less than 0.05 was considered significant. Results: A total of 667 hospitalized patients with COVID-19 were enrolled in the study, of which 54.4% were male. The median age of patients was 63 years old. About 39.4% of patients had hyponatremia on admission day. More than 80% of patients had mild hyponatremia. The median age of the hyponatremia group was significantly higher than that of eunatremia group. Conclusion: Our data showed that hyponatremia is observed in hospitalized patients with COVID-19 and is often mild.